Polymer Membranes for Gas Separation - Lasseuguette, Elsa; Comesaña-Gándara, Bibiana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on "Polymer Membranes for Gas Separation" of the journal Membranes aims to offer an overview about the different applications and strategies available to improve the separation performances based on the material choice and the process conditions.Various topics have been discussed, including the synthesis and characterization of novel membrane materials, membrane aging, and the impact of process conditions on transport phenomena.